Adaptive mutations of neuraminidase stalk truncation and deglycosylation confer enhanced pathogenicity of influenza A viruses - Park, Sehee; Il Kim, Jin; Lee, Ilseob; Bae, Joon-Yong; Yoo, Kirim; Nam, Misun; Kim, Juwon; Sook Park, Mee; Song, Ki-Joon; Song, Jin-Won; Kee, Sun-Ho; Park, Man-Seong (Scientific reports, 2017)
It has been noticed that neuraminidase (NA) stalk truncation has arisen from evolutionary adaptation of avian influenza A viruses (IAVs) from wild aquatic birds to domestic poultry. We identified this molecular alteration after the adaptation of a 2009 pandemic H1N1 virus (pH1N1) in BALB/c mice. The mouse-adapted pH1N1 lost its eight consecutive amino acids including one potential N -linked glycosite from the NA stalk region. To explore the relationship of NA stalk truncation or deglycosylation with viral pathogenicity changes, we generated NA stalk mutant viruses on the pH1N1 backbone by reverse genetics. Intriguingly, either NA stalk truncation or deglycosylation changed pH1N1 into a lethal virus to mice by resulting in extensive pathologic transformation in the mouse lungs and systemic infection affecting beyond the respiratory organs in mice. The increased pathogenicity of these NA stalk mutants was also reproduced in ferrets. In further investigation using a human-infecting H7N9 avian IAV strain, NA stalk truncation or deglycosylation enhanced the replication property and pathogenicity of H7N9 NA stalk mutant viruses in the same mouse model. Taken together, our results suggest that NA stalk truncation or deglycosylation can be the pathogenic determinants of seasonal influenza viruses associated with the evolutionary adaptation of IAVs.